Disability in Iran: Prevalence, Characteristics, and Socio-Economic Correlates - Homeira Sajjadi; Nasibeh Zanjari (University of Social Welfare and Rehabilitation Sciences, 2015)
Objective: The main purpose of this study was to investigate the prevalence and socio-economic correlates of disabilities in Iran. Materials & Methods: Secondary analysis of aggregate and micro data (in individual and household level) from the Iranian 2006 census is used. Micro-data collection contains representative sample including 19,848 disabled people and 1,235,445 non-disabled people in individual level, and 17,166 households with a disabled person and 298,741 households with non-disabled person in household level. Bivariate and multivariate statistical analyses were used for data analysis with SPSS software. Results: The prevalence of disability was 14.4 per 1000 in Iran. Disability was higher in rural area than in urban area, and also, was more common among men than women. Research findings show disabled people had lower levels of socio-economic status compared to non-disabled people. In addition, results indicated economic and welfare status of household was statistically significant association with disability. Logistic regression analysis showed that female-headed households were more likely to have a disabled person in the household. And also, the education and occupation of the head of the household, welfare index of household and rural-urban residence were significantly associated with having a disabled person in the household. Conclusion: Low levels of welfare and poor living conditions of households increase the likelihood of disability. Thus, social welfare programs for lower income and vulnerable households and also delivery specific services packages for disabled people are recommended.